2016
DOI: 10.1515/jomb-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of AdipoR1 is Associated with Increased Circulating Adiponectin Levels in Serbian Chronic Kidney Disease Patients

Abstract: SummaryBackgroundSince the rise in plasma adiponectin levels in chronic kidney disease (CKD) patients has not yet been elucidated, we sought to investigate if patients on hemodialysis (HD) have altered expression of adiponectin receptors in peripheral blood mononuclear cells (PBMCs) compared to healthy subjects.MethodsThis study included 31 patients with chronic kidney disease on HD and 33 healthy subjects (CG). Circulating adiponectin levels were measured by ELISA while AdipoR1 and AdipoR2 mRNA levels in PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…In CKD patients, higher adiponectin concentrations which are usually more than three times higher compared with healthy individuals are associated with poor outcomes and increased mortality (21). Result of our study confirmed previous founding (19, 22) that the high levels of adiponectin decline after renal transplantation ( Table II ). Also, we found significant positive correlation between adiponectin concentration and presence of smaller HDL 3b particles ( Table III ), so we could speculate that even adiponectin is presumed to possess antiatherogenic properties in the uncommon uremic milieu, higher adiponectin levels are associated with increased risk for cardiovascular disease development.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In CKD patients, higher adiponectin concentrations which are usually more than three times higher compared with healthy individuals are associated with poor outcomes and increased mortality (21). Result of our study confirmed previous founding (19, 22) that the high levels of adiponectin decline after renal transplantation ( Table II ). Also, we found significant positive correlation between adiponectin concentration and presence of smaller HDL 3b particles ( Table III ), so we could speculate that even adiponectin is presumed to possess antiatherogenic properties in the uncommon uremic milieu, higher adiponectin levels are associated with increased risk for cardiovascular disease development.…”
Section: Discussionsupporting
confidence: 92%
“…Even it is good known that adiponectin has cardio protective and anti-inflammatory effects, the role of this adipocytokine in patients with CKD are still unclear (19). Results of previous studies have confirmed a positive association between adiponectin concentration and progression of CKD (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two possible explanations could be postulated. One, the low plasma adiponectin level, which could have an anti‐protective effect on CRC prognosis, might have compensatorily resulted in the upregulation of the adiponectin receptor mRNA level in the CRC tissue . Second, the increased ADIPOR1 mRNA expression level implies increased adiponectin bioavailability, which has a pro‐angiogenesis effect, resulting in the progression of CRC and poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…So in our study, the cause of high level of MIOX in AKI patients may be related to increased to ROS. Because it is also known that there is an association with oxidative stress and AKI (19, 20).…”
Section: Discussionmentioning
confidence: 99%